Hypercobalaminemia in recalcitrant oral ulcers: A case report and literature review - Nisaa, Ihda R.; Putri, Andi AM.; Marlina, Erni; Usman, Nur A. (Hasanuddin University, 2024)
Objective: This article aims to report an interesting rare case of recurrent oral ulceration with a high level of cobalamin.Case report: A 44-year-old female came to dental clinic with chief complaint of recalcitrant oral ulceration since half a year ago. Patients basically had history of periodic oral ulcer for quite long time with short occurrence and only one or two ulcer in one period. However, the ulcer become alarming after she was hospitalized due to extreme fatigue. Patients subsequently instructed for routine blood along with cobalamin and IgE total examination. The test came back with highly decreased level of red blood index indicates that the patients on severe anemic condition. Unexpectedly, the levels of cobalamin in blood increased by 70% from the referral score. Patients urgently refer for hospitalization to recover her Hb level. After blood transfusion, patients discharged from the hospital but under hematologic observation for the exact etiology of her anemia, including the high cobalamin level. After two months observation, patients Hb gained normal level, however the vitamin B12 level remain. Patients reported decreased in number of ulcers.Conclusion: It is worthy to always check on cobalamin level for patients with recurrent oral ulcers since lower level can directly causing it or the high level can lead to some life-threatening diseases which can also trigger the recalcitrant oral ulcers.